Parenting centers and caregiver mental health: Evidence from a large‐scale randomized controlled trial in China. Issue 5 (28th April 2022) - Jiang, Qi; Dill, Sarah‐Eve; Sylvia, Sean; Singh, Manpreet K.; She, Xinshu; Wang, Eric; Medina, Alexis; Rozelle, Scott
Abstract: This study conducts an exploratory analysis of the impacts of a center‐based early childhood development intervention on the mental health of caregivers, using data from a cluster‐randomized controlled trial of 1664 caregivers ( M age  = 36.87 years old) of 6‐ to 24‐month‐old children in 100 villages in rural China. Caregivers and children in 50 villages received individual parenting training, group activities and open play space in village parenting centers. The results show no significant overall change in caregiver‐reported mental health symptoms after 1 year of intervention. Subgroup analyses reveal heterogeneous effects by caregiver socioeconomic status and identity (mother vs. grandmother). Findings suggest that early childhood development interventions without targeted mental health components may not provide sufficient support to improve caregiver mental health.